Primary cardiac sarcoma: a case report of a therapeutic challenge. Issue 6 (7th December 2020) - Andrei, Valentina; Scheggi, Valentina; Stefàno, Pier Luigi; Marchionni, Niccolò
Abstract: Background: Primary cardiac sarcomas are very rare and the prognosis is poor both because the diagnosis is typically made at an advanced stage of the disease and because data are insufficient to identify a standard treatment. Surgical resection is the cornerstone of therapy with the need to develop new therapeutic strategies. Case summary: We present a case of a young man admitted to the emergency department due to worsening dyspnoea. A left-sided sarcoma was diagnosed and treated with surgery, chemo- and radiation therapy, and subsequently with heart transplant for local recurrence of the disease. Endomyocardial biopsy made during the routine follow-up period was complicated by pericardial tamponade and cardiogenic shock and the patient was managed with veno-arterial extracorporeal membrane oxygenation, until recovery of left ventricular function (left ventricular ejection fraction of 55%). After 1 year a kidney transplant was performed. After 42 months from diagnosis, the patient is in good general condition. Discussion: Primary cardiac sarcomas are treated with surgery to reach R0 (free resection margins) and with chemo- and radiation therapy with adjuvant purposes. Auto-transplantation is also performed, while conventional heart transplant must be customized on an individual basis, after excluding metastases. A multidisciplinary assessment should be performed and the single patient treated with a personalized approach, in relation to his performance status, location of the mass, and stage of the disease.